Aktivitas Antibakteri dari Sinularia sp. terhadap Escherichia coli dan Staphylococcus aureus: Meta-analisis dan Telaah Sistematis: Antibacterial Activity of Sinularia sp. Against Escherichia coli and Staphylococcus aureus: Meta-Analysis and Systematic Review - Prismawan, Deka; Monika Arvia Chiara; Shannen Ivanka Gunardi; Karmill Trinanda; Robby Sutedjo; Michael, Michael (Journal of Health (JoH), 2025)
The Ocean covers more than 70% of Indonesian archipelago, providing various bioactive compounds with great potential, however, it is relatively underexplored Sinularia sp, a genus of soft corals, exists at the coral reefs of Indo-Pacific ocean. Several recent studies have shown that Sinularia sp. contains various types of secondary metabolites with antiviral, antibacterial, anticancer, and antimalarial properties. In addition, further exploration and discovery of novel antibacterials that are effective against wide spectrum of bacteria is of great interest, especially to combat the emerging antibiotic resistance. The aim of this study is to evaluate the potential of antibacterial activity from Sinularia sp against E. coli and S. aureus which in turn, may provide an alternative antibacterial to overcome the emerging antibiotic resistance. This study was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement to measure the effect size of the antibacterial activity from Sinularia sp. against E. coli and S. aureus. Estimated value of the effect size obtained is 2.52 (CI 95% 0.98 to 4.06) and 5.97 (CI 95% 3.18 to 8.77) towards E. coli and S. aureus. When viewed as a whole, published data appears to show a positive antibacterial effect from Sinularia sp.